Love everyone: the transcendent wisdom of Neem Karoli Baba told through the stories of the Westerners whose lives he transformed - Parvati Markus (New York: Harper Collins, 2015)
"A celebration of one of the most influential spiritual leaders of our time, Neem Karoli Baba, the enlightened guru who inspired a generation of seekers--including Ram Dass, Daniel Goleman, and Larry Brilliant--on life-altering journeys that helped change the world.In 1967, Ram Dass returned to the West from India and spread the teachings of his mysterious guru, Neem Karoli Baba, better known as Maharajji. Ram Dass's words about Maharajji's life-affirming wisdom resonated with a youth culture that had grown disillusioned with the violence, civil discord, and crude materialism of modern civilization. Hundreds of Westerners travelled to India and experienced Maharajji's extraordinary presence directly until his death in 1973. His simple directives--love everyone, feed everyone, and remember God--opened their hearts and awakened their souls.What these followers brought back to the West has since changed the landscape of everyday life. Meditation is now mainstream; yoga studios are in every town; and mindfulness is practiced in elementary schools and boardrooms everywhere from Silicon Valley to Capitol Hill. A stirring piece of history, Love Everyone brings these stories to life, sharing for the first time the inspiring tales of the men and woman who followed the siren call of the East to the foothills of the Himalayas, then returned to forever reshape the world.A compelling and inspiring tribute to Maharajji from the Western men and women who knew him best, Love Everyone is a profound teaching on the power of love, as lasting and transformative as the truth, wisdom, and bliss of Maharajji. Parvati Markus is a developmental editor and writer of spiritually oriented non-fiction books and memoirs. She has worked on books by various members of the satsang, from Ram Dass's classic Be Here Now (before she went to India) to those since her time in India with Maharajji (1971-72)--Dada Mukerjee's By His Grace and The Near and the Dear to Krishna Das's recent Chants of a Lifetime. She is a former President of the Board of the Neem Karoli Baba Ashram and Temple and a former development consultant for the Global Peace Initiative of Women Religious and Spiritual Leaders, held at the U.N. in Geneva, Switzerland. She lives in West Palm Beach, Florida"--
Keywords: Biography Neem Karoli Baba; Spiritual Biography; Hinduism; Religion